2010
DOI: 10.1002/jso.21533
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and prognosis of mucinous gastric carcinoma

Abstract: MGC is rare and detected mostly in an advanced stage. Mucinous histology type itself is not an independent prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Zhang et al (6) suggested that tumor size, depth of invasion and lymph node metastasis were not associated with MGC and NMGC. However, we observed that MGC and NMGC differed in tumor size, macroscopic type, lymphovascular invasion, peritoneal metastasis and TNM stage, which was in agreement with the findings of Adachi et al (7) and Yin et al (14).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (6) suggested that tumor size, depth of invasion and lymph node metastasis were not associated with MGC and NMGC. However, we observed that MGC and NMGC differed in tumor size, macroscopic type, lymphovascular invasion, peritoneal metastasis and TNM stage, which was in agreement with the findings of Adachi et al (7) and Yin et al (14).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Undifferentiated gastric carcinomas are generally associated with a worse prognosis (3). Mucinous gastric carcinoma (MGC) is a rare histological subtype of undifferentiated gastric carcinoma, accounting for 2.6-6.6% of all gastric cancer cases (4)(5)(6)(7)(8). The available literature on MGC is currently limited, mostly due to its rarity.…”
Section: Introductionmentioning
confidence: 99%
“…The innate characteristics and prognosis of MAC and SRC have been studied [5-18]. However, the results of those studies are still debated.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the incidence of early cases was only 20.0% in MGC, while among other pathological types of carcinoma, 44.6% were diagnosed at an early stage [4]. In contrast to these reports, some investigators have reported a similar incidence of early MGC and early NMGC cases (10.4% vs. 10.8%) [11]. In the present study, early MGC cases were 14.4% of all early gastric carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed to explain why MGC is almost always diagnosed at a late stage [15]. In contrast, some investigators have found no significant difference between the overall survival rates of early MGC and early NMGC [11,13]. Furthermore, some studies have reported that the surgical outcome is better for patients with early MGC than for patients with early NMGC [7,12].…”
Section: Discussionmentioning
confidence: 99%